The Oxford handbook of public choice / volume 2 - Congleton, Roger D.; Grofman, Bernard; Voigt, Stefan (The Oxford handbook of public choice, 2019)
The two volume Oxford Handbook of Public Choice provides a comprehensive overview of the Public Choice literature. Volume 2 covers constitutional political economy and applications of public-choice models to various policy areas. Part V has chapters on the architecture of governance, the theory of dictatorship, and the effects of the institutions of governance. Part VI discusses the politics of public policy, international public choice, public choice and history, and measurement issues. The volume touches on topics such as taxation, redistribution, federalism, and monetary policy. It ends with discussions of various methodological approaches, including extensions of the core models to account for altruism and trust, and overviews of measurement and estimation issues, and the use of experiments in public-choice research.